Reuse into housing: Italian and Dutch regulatory effects. Issue 2 (18th April 2017) - Olivadese, Rosamaria; Remøy, Hilde; Berizzi, Carlo; Hobma, Fred
Abstract : Purpose: The need to speed up and simplify the practice of transformation and the topic of reuse is crucial in Italy. The purpose of this paper is to compare successful cases of reuse into housing in Italy and the Netherlands, in order to suggest improvements to the Italian situation. Design/methodology/approach: Previous research at the University of Pavia showed the need to change living standards for new residential buildings. This research focusses on existing buildings and gives a comparative analysis of the Italian and Dutch legislation for residential buildings. Interviews with professionals have been conducted in Italy and the Netherlands to better understand the differences and problems related to housing regulations. Good examples of reuse into housing have been studied to define common guidelines for intervention. Findings: The findings describe the building regulations in Italy and the Netherlands concerning adaptive reuse, and reveals differences between the two countries. Furthermore, the possibilities and barriers for the reuse of existing buildings are highlighted. Practical implications: Lessons are drawn from both contexts, and finally suggestions for improvement of the regulatory system are made for Italy and the Netherlands. Originality/value: This paper aims at revealing the opportunities and barriers of reuse in Italy and the Netherlands. So far, studies were performed to reveal the feasibility of adaptive reuse, though none of these focussed specifically on legal issues. No sufficient studies are performed so far on reuse into housing in Italy, and the comparison of the regulatory systems of the two countries is novel.